The effects of entrepreneurial orientation, social media, managerial ties on firm performance: Evidence from Vietnamese SMEs - An Thi Hong Nguyen (Growing Science, 2022)
This study examines the effects of entrepreneurial orientation, social media, and managerial ties on the business performance of small and medium-sized enterprises (SMEs) in Vietnam. In addition, the mediating effects of social media and managerial ties on the causal relationship between entrepreneurial orientation and firm performance is investigated. A total of 180 senior managers of SMEs were collected for data analysis by using partial least squares structural equation modeling. The results reveal that entrepreneurial orientation strongly enhances social media and managerial ties, which are determinants of business performance. Specifically, entrepreneurial orientation has no direct impact on firm performance; but the mediating effects were confirmed. Based on the results, our study highlights some theoretical contributions and suggests practical implications for practitioners in Vietnamese SMEs to improve firm performance effectively and efficiently.